Cognitive, Metacognitive, or Social: Which Learning Strategies Do Arabic Language Learners Prefer? - Sholihah, Diana Nur; Auliya, Lulu Marfuatin; Nabiilah, Salmaa; Alfiyah, Siti Salwa (Langkawi: Journal of The Association for Arabic and English, 2025)
This research aims to explore how Arabic learners at Universitas Islam Tribakti Lirboyo Kediri utilize language learning strategies (LLSs) and whether gender influences their strategic preferences. The participants consisted of 100 students—40 male and 60 female—who completed the Language Learning Strategy Questionnaire (LLSQ) developed by Rita et al. (2019). The instrument asked students to reflect on how frequently they use specific strategies—cognitive, metacognitive, and social—when learning the four core Arabic language skills: speaking, listening, reading, and writing. The findings revealed that cognitive strategies were the most frequently used across most skill areas. Metacognitive strategies appeared more prominently in writing tasks, while social strategies—such as seeking help from peers—were generally used less often. Interestingly, statistical analysis indicated no significant gender differences in strategy use, suggesting that both male and female students approach language learning in relatively similar ways. These patterns point to a strong reliance on task-based strategies, with comparatively less emphasis on reflective or collaborative approaches. In light of these results, educators may consider supporting learners in diversifying their strategy use—particularly by promoting peer interaction and strategic planning behaviors—to foster deeper and more effective language learning.